1974
DOI: 10.1042/cs0470143
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function in Chronic Uraemia before and after Removal of Excess of Fluid by Haemodialysis

Abstract: 1. Measurements of lung volumes, airway resistance, maximal expiratory flow rates and closing volume were made in twelve patients with chronic renal insufficiency and fluid overload, before and after haemodialysis.2. Before dialysis, these measurements were within normal limits, except for peak expiratory flow rate, which was significantly lower, and closing volume, which was significantly higher than predicted values.3. After dialysis body weight decreased significantly and the removal of excess of fluid was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, in early studies on small numbers of patients, removal of marked excess body water, i.e. up to 9.6% of body weight [26], resulted in significant improvement or normalization of decreased lung volume [17,21,26]. The weight gain in our patients was significantly less (1.2-4.4 kg or 2-6% of body weight) and all patients with irreversible restrictive lung function had a history of severe pulmonary disease or heart failure.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, in early studies on small numbers of patients, removal of marked excess body water, i.e. up to 9.6% of body weight [26], resulted in significant improvement or normalization of decreased lung volume [17,21,26]. The weight gain in our patients was significantly less (1.2-4.4 kg or 2-6% of body weight) and all patients with irreversible restrictive lung function had a history of severe pulmonary disease or heart failure.…”
Section: Discussionmentioning
confidence: 63%
“…The intrasubject repeatability was less than 5%, which gives values low enough to detect significant responses to removal of excess water or biocompatibility-induced airway hyper-reactivity. Some studies investigating spirometric lung function in the dialysis population found no changes in VC, FEV1 and FEF25-75% before and at the end of a dialysis session using bioincompatible membranes [14,17,21], therefore it has been stated that in end-stage renal disease patients on hemodialysis lung volumes and flow rates are normal unless there is chronic pulmonary or chest-wall disease. However, in early studies on small numbers of patients, removal of marked excess body water, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Such patients often require prolonged ven tilatory assistance even after they achieve pulmonary function adequate for weaning (e.g., normalization of tidal volume, blood gas levels, or respiratory muscle competence). Both lung function per se and chemoregulation of ventilation are normal in most stable uremic subjects [6][7][8] and thus do not explain these findings.…”
mentioning
confidence: 42%
“…These changes in pulmonary function bore some resemblance to the abnormalities observed in patients with heart diseases in the present study and may suggest that early pulmonary congestion or oedema may cause an increase in dependent airway closure with increase in closing volume. A study of patients with chronic uraemia provides some support for this hypothesis (Stanescu, Veriter, Plaen, Frans, Strihou & Brasseur, 1974). Closing volume was increased above normal values in.the patients studied by Stanescu et al (1 974) and fluid removal by haemodialysis was accompanied by significant reduction in closing volume.…”
Section: Closing Volume and Fluid Overloadmentioning
confidence: 80%